Tissue Toxicity Threatens the Gold Standard Image of Lithium as a Mood Stabilizer Drug (Medical Forum Monthly, 2024)
Objective: To demonstrate that the lithium is generally a toxic agent to tissues of both animals and humanbeings but especially to liver and kidney.Study Design: It is prospective, interventional, morphometric and theoritico-emperical study.Place and Duration of Study: This study was conducted at the Basic Medical Sciences Institute, Jinnah Post Graduate Medical Centre Karachi University, Karachi, Sindh from October 2012 to March 2013.Materials and Methods: 30 Albino rats were nursed under all necessary parameters and under the study plan were exposed to lithium carbonate with 20mg per Kg body weight per day. Under the study plan, rats were divided into two groups A and B, each group comprising of 15 rats. Group A is control group while group B is Experimental group exposed to lithium dose. Animals were killed after duration of two, six and twelve week’s exposure to lithium dosage as each group was divided into three sub groups each comprising of five animals.Results: Results of this study highlighted the fact that Lithium as the toxic metal displays significant toxic liver manifestations and disturbs the cytoarchitecture significantly along with the disturbances in the carbohydrates, protein, and fat metabolism. Alkaline phosphatase enzyme displays significant disruption therefore needs extensive evaluation for not only the hepatotoxicity but also biotoxicity and ecotoxicity.Conclusion: conclusively inference can be made that the lithium has lost its reputation as gold-standard mood stabilizer drug but can be employed as an investigative tool in Physiology. Biochemistry,Genetics and Pharmacology but particularly in Psycho-neurology